Treading The Footsteps of Wali Songo as The Shaper of Islam Nusantara Tradition - Siti Muliana; Muhammad Nasruddin (Sunan Kalijaga: International Journal of Islamic Civilization, 2021)
The focus of this article is to examine the footsteps of Wali Songo in shaping the tradition of Islam Nusantara. As is known, the Wali Songo period was a period of formation of the Nusantara Islamic tradition which began in the 14th century AD. This topic is considered important because the period of formation of the Nusantara Islamic tradition needs to be relevant to today's diversity. In addition, the purpose of choosing this topic is also a response to the religious attitudes of contemporary Islamic society and the various notions that have emerged under the pretext of the Nusantara Islam tradition, which is forbidden because of shirk and superstition. Studying based on socio-historical aspects is the study method used in writing this article. The conclusions reached are, first, Wali Songo is the main agent who plays a major role in shaping the tradition of Islam Nusantara. Second, there are three efforts by Wali Songo in shaping the tradition of Islam Nusantara, nameky prioritizing religious substance rather than formality, spreading religious substance through popular culture, and prioritizing opennes to local traditions.